Comorbidity, sex and age as risk conditions for severe COVID-19 in teachers of a university in northern Perú - Isla-Grados, Soledad (2023)
Background: In Peru, the high lethality from COVID-19 demands the identification of serious conditioning factors at the community level. Objective: To determine if comorbidity, sex, and age are associated with the severity of COVID-19 in university professors. Material and methods: Prospective cohort study in 115 teachers who met eligibility criteria, clinical and laboratory follow-up. Exposure data was obtained through an online questionnaire and medical evaluation. COVID-19 was confirmed with laboratory results and severity status by telephone interview and home medical visit. Association was sought using the generalized linear model. Results: 30.43% presented COVID-19; incidence: 2 infected cases/100 teachers/week of follow-up. The probability of non-contagion by COVID-19 was analyzed in week seven, it was 87.83%, at week 24 it decreased to 69.57%. The severity rate reached 22.9%, more frequent in men and hypertensive patients. Although a non-significant association was determined between the severity of COVID-19 and the male sex [IRR=3.65; 95%CI (0.45–29.68)], age older than 50 years [IRR=0.56; 95%CI(0.14–2.37)], arterial hypertension [IRR=1.76; 95%CI(0.42–7.38)], Diabetes [IRR=2.36; 95%CI(0.29–19.16)] and Obesity [IRR=0.27; 95% CI (0.03–2.22)], the number of participants does not allow us to confirm this. Conclusions: Due to the few data analyzed, it is not possible to indicate that there is a significant association between comorbidity, male sex, age over 50 years and the severity of COVID-19. It is necessary to continue studying these factors with larger samples, in order to reduce the disease burden and/or mortality from COVID-19.